Let's take bargaining models seriously: The decline in union power in Germany, 1992 - 2009 - Boris Hirsch; Claus Schnabel (Institute for the Study of Labor (IZA), 2011)
Building on the right-to-manage model of collective bargaining, this paper tries to infer union power from the observed results in wage setting. It derives a time-varying indicator of union strength and confronts it with annual data for Germany. The results show that union power was relatively stable in the 1990s but fell substantially (by almost one-third) from 1999 to 2007. Two-thirds of this fall in union power follow from the reduction in the labour share relative to the capital share whereas changes in the gap between the net wage and the income when unemployed account for the remaining third.
urn:nbn:de:101:1-201108093027
Keywords: J50; J51; 330; trade union power; wage bargaining; labour share; Germany